Enhancing Primary Care Delivery: A Comprehensive Review of Collaboration among Multidisciplinary Teams - Alhumainy, Noura; Alnajrani, Turki Mohammad; Thobaiti, Abdullah Ayedh Al; Alharthi, Ali Abdullah Abdulaziz; Alkhalide, Hani Modkil; Alghamdi, Jihan Dawi Saad; Alharthi, Najmah Saqer; Alotaibi, Abdullah Aedh Ghazi; Aldajani, Hind Mohammed Hamoud; Al-Tarad, Reem Dhafer Saad (Journal of Posthumanism, 2024)
Enhancing primary care delivery increasingly depends on the strength of collaboration among multidisciplinary teams (MDTs), especially as patient needs grow more complex and chronic diseases become more prevalent. This review synthesizes contemporary evidence on how coordinated teamwork among physicians, nurses, pharmacists, allied health professionals, social workers, and care coordinators improves the accessibility, safety, and efficiency of primary care. A structured search across major scientific databases identified empirical studies published between 2016 and 2025 examining team-based models, collaborative mechanisms, and resulting clinical and organizational outcomes. Findings show that MDT collaboration significantly enhances chronic disease management, medication optimization, patient education, and preventive care delivery. Patients benefit from better continuity, improved satisfaction, and greater self-management capacity, while healthcare organizations experience reduced fragmentation, fewer unnecessary hospital visits, and more efficient resource utilization. However, the review also reveals persistent challenges, including role ambiguity, communication gaps, variable leadership structures, and limited health information integration. Overall, the evidence supports MDT collaboration as a foundational driver of high-quality, patient-centered primary care, provided that systems invest in clear governance structures, interoperable digital tools, and continuous interprofessional training. Strengthening these collaborative mechanisms is essential for achieving resilient, integrated, and sustainable primary care models worldwide.